American Society of Civil Engineers index to transections vol 1. - American Society of Civil Engineers; American Society of Civil Engineers (New York, American Society of Civil Engineers.)
Vols. 131 include papers of the International Engineering Congress, Chicago, 1965; v. 54 includes papers of the International Engineering Congress, St. Louis, 1904.
0
SERBIB/SERLOC merged record
Keywords: Civil engineering